This paper deals with a boundary value problem for a nonlin- ear di erential equation with two conformable fractional derivatives and integral boundary conditions. The results of existence, uniqueness and stability of positive solutions are proved by using the Banach contrac- tion principle, Guo-Krasnoselskii's xed point theorem and Hyers-Ulam type stability. Two concrete examples are given to illustrate the main results. Mathematics Subject Classi cation (2010): 47H10, 26A33, 34B18. - Djiab, Somia (Université de M'sila, 2021)
This paper deals with a boundary value problem for a nonlin- ear di erential equation with two conformable fractional derivatives and integral boundary conditions. The results of existence, uniqueness and stability of positive solutions are proved by using the Banach contrac- tion principle, Guo-Krasnoselskii's xed point theorem and Hyers-Ulam type stability. Two concrete examples are given to illustrate the main results.
Keywords: Conformable fractional derivatives, Positive solutions, Fixed point theorems, Hyers-Ulam stability.